2011
DOI: 10.1071/fp11023
|View full text |Cite
|
Sign up to set email alerts
|

Ecological implications of organic carbon dynamics in the traps of aquatic carnivorous Utricularia plants

Abstract: Rootless aquatic carnivorous Utricularia exude up to 25% of their photosynthates into the trap lumen, which also harbours a complex microbial community thought to play a role in enhancing Utricularia nutrient acquisition. We investigated the composition of organic carbon in the trap fluid, its availability for microbial uptake, the influence of plant nutrient status and trap age on its biodegradability, and the composition of prokaryotic assemblages within the traps of three aquatic Utricularia species. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 55 publications
5
51
1
Order By: Relevance
“…; Sirová et al. ). However, very little is known about their specific interactions and their roles in plant life cycle and nutrition.…”
Section: Physico‐chemical Properties Of the Environment Inside Utricumentioning
confidence: 96%
See 3 more Smart Citations
“…; Sirová et al. ). However, very little is known about their specific interactions and their roles in plant life cycle and nutrition.…”
Section: Physico‐chemical Properties Of the Environment Inside Utricumentioning
confidence: 96%
“…; Sirová et al. , ), several authors reported the occurrence of highly abundant populations of mixotrophic ciliates (e.g. Płachno et al.…”
Section: Physico‐chemical Properties Of the Environment Inside Utricumentioning
confidence: 99%
See 2 more Smart Citations
“…2; Raven et al 2009). We do not consider carnivorous angiosperms in detail here, but note that they are photosynthetic (Juniper et al 1989;Raven et al 2009;Król et al 2012), can take up organic C in amino acids and peptides via transporters (Schulze et al 1999) and via endocytosis (Adlassnig et al 2012), but have a significant C cost in trap construction and maintenance and in enzyme secretion (Ellison and Adamec 2011;Sirová et al 2011).…”
Section: Mixotrophy In Phytoplankton Other Aquatic Organisms and Termentioning
confidence: 99%